Assessment of Plant Diversity of a Seasonal Tropical Wetland Forest Ecosystem in Bangladesh - Saha, Sajal; Pavel, Muha Abdullah; Uddin, Mohammad Belal (Borneo Journal of Resource Science and Technology, 2018)
The quantitative analysis of plant diversity was explored on a seasonal tropical wetland forest ecosystem at Ratargul Swamp Forest. The simple random sampling protocol was adopted, and 30 plots (10 m×10 m) each with one subplot (2 m×2 m) was investigated for the vegetation survey. The study found about 539 individuals of 48 species belonging to 36 families. Poaceae was the dominant among all family. The upper (trees with all size) and lower (shrubs, herbs, climbers, grasses) stratum was dominated by Pongamia pinnata and Clinogyne dicotoma, respectively. The taxonomic diversity was moderate in both lower and upper strata. The value of floristic quality index was calculated at 19.92, which represents moderate vegetative quality. The outcome also revealed the disturbances which influenced the plant community, mostly due to branch cutting by human (<30%). The findings will be useful for the conservation and scientific management of biodiversity as a hotspot in seasonal tropical wetland forest system. Keywords: Biodiversity, conservatism, disturbance, hotspot, wetland